A Low-Cost Inkjet-Printed Aptamer-Based Electrochemical Biosensor for the Selective Detection of Lysozyme - Khan, Niazul Islam (Biosensors (Basel), 2018)
Recently, inkjet-printing has gained increased popularity in applications such as flexible electronics and disposable sensors, as well as in wearable sensors because of its multifarious advantages. This work presents a novel, low-cost immobilization technique using inkjet-printing for the development of an aptamer-based biosensor for the detection of lysozyme, an important biomarker in various disease diagnosis. The strong affinity between the carbon nanotube (CNT) and the single-stranded DNA is exploited to immobilize the aptamers onto the working electrode by printing the ink containing the dispersion of CNT-aptamer complex. The inkjet-printing method enables aptamer density control, as well as high resolution patternability. Our developed sensor shows a detection limit of 90 ng/mL with high target selectivity against other proteins. The sensor also demonstrates a shelf-life for a reasonable period. This technology has potential for applications in developing low-cost point-of-care diagnostic testing kits for home healthcare.